2007
DOI: 10.1143/apex.1.013001
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling Current–Voltage Characteristics of Graphene Field-Effect Transistor

Abstract: We present an analytical device model for a field-effect transistor based on a heterostructure which consists of an array of nanoribbons clad between the highly conducting substrate (the back gate) and the top gate controlling the source-drain current. The equations of the model of a graphene nanoribbon field-effect transistor (GNR-FET) include the Poisson equation in the weak nonlocality approximation. Using this model, we find explicit analytical formulas for the spatial distributions of the electric potenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…(2) is neglected [17,18], so that the relationship between the potential in the channel and the electron and hole charge becomes local. The harnessing of the approximation under consideration makes, in particular, possible an analytical study of essentially nonuniform potential distributions in the NGR-FET channel and the short-gate effects [13].…”
Section: Potential Distribution Along the Gfet Channelmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) is neglected [17,18], so that the relationship between the potential in the channel and the electron and hole charge becomes local. The harnessing of the approximation under consideration makes, in particular, possible an analytical study of essentially nonuniform potential distributions in the NGR-FET channel and the short-gate effects [13].…”
Section: Potential Distribution Along the Gfet Channelmentioning
confidence: 99%
“…The current associated with the interband tunneling processes near the tunneling points t x x = ± is given by [10,11,13] …”
Section: Wwmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the existing physical models of graphene for electrical charge and conduction, the first-principle calculation of tunneling effects, band structures, and carrier transport, however, get the superlative ponderosity [15]- [16]. But, complex numerical calculations are required to find out tunneling current distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The detector proposed has a structure of GNR field-effect transistor consisting of an array of GNRs with the side source and drain contacts (to each GNR) sandwiched between the highly conducting substrate and the top gate electrode. The operation of devices with similar structure were explored recently (see, for instance, [17,18,19,20,21,22,23]). Here, we study The structure of GNR-PT under consideration is schematically shown in Fig.…”
mentioning
confidence: 99%